Pemanfaatan Media Sosial Instagram @agendasolo sebagai Media Informasi bagi Masyarakat Surakarta - Safitri, Desi Nur; Itasari, Andri Astuti (Solidaritas, 2024)
The Ministry of Communication and Information Technology reported that by the end of 2023, there were 1,615 hoax issues on social media, including hoaxes about special event purportedly organized by the Ministry of Tourism and Creative Economy (Kemenparekraf RI), which have caused public concern. This study aims to investigate the utilization of the Instagram account @agendasolo as an information medium for the people of Surakarta. The method used is descriptive qualitative. Primary data collection was conducted through observation, interviews, and documentation, while secondary data collection utilized online sources. The data validity technique employed was source triangulation. The theory used is Chris Heuer's 4C Social Media Management Theory, which consists of Context, Communication, Collaboration, and Connection. The findings of this study indicate that the Instagram account @agendasolo is beneficial in providing various types of information about the city of Surakarta by utilizing existing features and considering important aspects of social media management, namely Context, Communication, Collaboration, and Connection. Thus, the Instagram account @agendasolo serves as a valuable social media account and information source for the people of Surakarta. Keywords: Instagram, Social Media, Information Source, Instagram Account @agendasolo